Exploring the challenges in following nutrition recommendations among malaysians with early stages of chronic kidney disease (ckd) - Mohamad Hasim, Muhamad Hishamudin; Lim, Yin Sze; Cheng, Shi-Hui; Lim, Christopher Thiam Seong (Qualitative Research Association of Malaysia, 2023)
Chronic kidney disease (CKD) is a significant global public health problem. Despite the growing burden of CKD and its accompanying co-morbidities, the difficulties faced by the CKD population in Malaysia, particularly those who are in the early stages of the disease, have not yet been identified. Hence, a qualitative study was undertaken to identify the challenges faced by CKD patients in following nutrition recommendations. Eight patients diagnosed with early stages of CKD (stages 2 and 3) were recruited to undergo in-depth semi-structured interview sessions consisting of open-ended questions were conducted. Responses given in Malay were recorded verbatim and were translated into English. The data was analysed thematically with NVivo version 12 software. Five themes emerged from the interviews: 1) CKD health literacy, 2) changes in lifestyle and eating behaviours, 3) challenges in following CKD recommendations, 4) nutrition education perceptions and preferences, and 5) quality of life. The major challenges encountered by CKD patients in following nutrition recommendations were a lack of knowledge of CKD, insufficient communication between patient and healthcare professional (dietitian), inadequate healthy food choices, and a lack of time to prepare healthy food. The majority of the patients had never heard of nutrition education, yet they all agreed that nutrition and health education were essential for CKD patients. In addition, positive support from family and friends was considered a key component in improving their personal needs and quality of life. From the findings, it is concluded that effective nutrition education should be developed and explained clearly to the patients in order to improve patients’ self-management and empower them to make appropriate food choices. This study can be useful for healthcare professionals and policymakers intending to implement nutrition education-related interventions in order to improve CKD patients’ knowledge and their quality of life.